Dangdut Music Therapy Effect on The Auditory Hallucination Patients - Ayu Arvintasia, Jesika Dini; Ulum, Mohamad Miftachul; Suprajitno, Suprajitno (Poltekkes Kemenkes Malang, Campus III Blitar, 2025)
Auditory hallucinations are a condition where a person experiences impaired auditory perception in the form of hearing false (unreal) sounds without any stimulation, so that patients need to be trained to control their hallucinations. Besides general therapy, there are several other ways to reduce patient's hallucination, one of the ways is by listening to dangdut music. The purpose of this study was to determine the response level of patients with auditory hallucinations before and after being given dangdut music therapy. The design of this study is quasi-experimental with a sample of 21 respondents according to predetermined criteria. Sampling used purposive sampling technique. The instrument used in this study was the AHRS (Audiotory Hallucination Rating Scale) questionnaire. Analyse using the Wilcoxon Signed Ranks test. Based on the results of the research, there was a significant effect in the form of a decrease in the level of response to auditory hallucinations before and after being given dangdut music therapy with a value of ? = 0.000 (? =<0.05), which means that the hypothesis can be accepted and it is proven that the effect is 100% or 21 patients experienced a decrease in the level of response to auditory hallucinations from moderate to mild level of response. Where when listening to dangdut music, the focus of the patient's attention will be diverted from the sounds of hallucinations. It is hoped that the decrease in the response rate of patients with auditory hallucinations after giving music therapy can be a consideration for non-pharmacological therapy for sufferers of auditory hallucinations.